Geodynamics of formation of the transition zone between the Dnieper–Donets basin and the Donbas foldbelt. Tectonic style of inversion deformations - Бартащук, О. В.; Суярко, В. Г.; Bartashchuk, A. V.; Suyarko, V. G. (Видавництво Львівської політехніки, 2020)
Мета. На підставі новітніх матеріалів геологічного картування дислокаційних поверхів осадового чохла Західно-Донецького грабена досліджено структурні прояви тектонічної інверсії рифтогенної структури у зоні її зчленування із Донецькою складчастою спорудою. Методика. З використанням структурно-кінематичного аналізу рисунків тектонітів різновікових структурних поверхів осадової товщі, з урахуванням інструментальних визначень напрямків тектонічних рухів за ними, вивчено тектонічний стиль та системну організацію колізійних деформацій Дніпровсько-Донецької западини. Результати. Показано, що складчасті деформації в трьох структурних поверхах, виділених у чохлі грабена – Герцинському, Ларамійському та Аттичному, контролювалися підкидо-насувними решітками і з істотною амплітудою горизонтальних рухів геомас у північних, північно-західних і південно-східних румбах. Тектонічний стиль інверсійних деформацій території перехідної зони визначається динамічно спряженими решітками тектонітів пізньогерцинського та альпійського (ларамійської та аттичної фаз) етапів тектогенезу, які контролюють ешелоновані покривно-насувні дислокації та кулісно зчленовану підкидоскладчастість у межах Західно-Донецького грабена. Наукова новизна. Вперше встановлено, що сукупність пластин та лусок тектонічних покривів та лінійна підкидо-складчастість разом із решітками тектонітів, які контролюють їх, утворюють на території грабена і перехідної зони систему тектонічного насування неодноразово дислокованих осадових геомас з південного сходу – від Донецької складчастої споруди, на північний захід – на слабкодислокований синеклізний автохтон западини. Головним структурним елементом покривно-складчастої системи визначено сегмент тектонічного вклинювання осадових геомас, ідентифікований за клиноформним структурним рисунком тектонітів. Північно-східний фланг сегмента сформований підкидо-складчастими зонами відкритих палеозойських структур – Торсько-Дробишевської, Північно-Донецької, Матросько-Тошківської, південно-західний – ешелонами лускатих тектонічних покривів насування. Вісь сегмента утворюють кулісні зчленовані ПетрівськоНовотроїцька, Велікокомишуваська, Дружківсько-Костянтинівська та Головна лінійні підкидо-антикліналі. Практична значущість. Аналіз системної організації інверсійних деформацій свідчить про руйнування рифтогенної структури в межах перехідної зони між Дніпровсько-Донецькою западиною та Донецькою складчастою спорудою. Структурним результатом тектонічної інверсії у південно-східній частині Дніпровсько-Донецької западини вважається формування Західно-Донецької покривно-складчастої тектонічної області. За стилем та інтенсивністю деформацій в її північній частині виділено Лугансько-Комишуваський район кулісної підкидо-складчастості, на півдні – Кальміус-Торецький район лускатих покривів насування. Це є підставою для коригування схеми регіонального тектонічного районування та основою для моделювання геодинаміки формування перехідної зони

Aim of the work is to conduct tectonophysical identification of the totality of the deformation structures of the collisional evolutionary stage, which determine the tectonic style of the Transition Zone between Dnieper-Donets Basin and the Donbas Foldbelt. Methods. For the research, we used the author's technique for reconstructing the fields of tectonic deformations and tectonophysical analysis of geostructures. The analytical base of the research was made up of new materials of geological mapping of the territory of the transition zone between the Basin and the Foldbelt. Results. Inversion deformations of the Dnieper-Donets Paleorift were controlled by lattices of tectonites of regionally stable submeridional directions of movements. The analysis of structural patterns of tectonites indicates the riftogenic faults of the basement in the sedimentary cover of the transition zone. They form echeloned stages of plumage, composed of thrusts with a significant component of horizontal displacement. The tectonic style of the Transition Zone is determined by the pushing on the low dislocation autochthon of the Basin which is repeatedly deformed, crumpled into the folds of sedimentary geomas from the Foldbelt. The allochthon structural and tectonic framework consists of thrusts, coulisse-jointed structural ensembles of thrusts, folded covers of transverse extrusion of geomas from axial to side zones, and folded covers of longitudinal thrust towards the depression. All together it forms the Western Donets Cover-folded Region, the main structural element of which is the Segment of the Tectonic Wedging of geomass. The north-eastern flank of the Segment is formed by such linear anticlinal zones, as Torsky-Drobishivska, North-Donets, Matrossko-Toshkovska. The south-western flank is composed of- Petrovsko-Novotroitska zone. The structural apex of the Segment is a tectonic junction at the ends of dynamically conjugated thrusts in the area of the joint of the salt-dome shafts of the axial part of the Basin. Scientific novelty. The tectonic inversion is responsible for the formation of three folded structural floors, including the Herzinian, Laramian and Attic floor. According to the dynamically coupled lattice, a cover-folding system of tectonic thrusting was formed in them. It was first established as a Segment of Tectonic Wedging of geomas by the Donbas Foldbelt. On the basis of this, within the Transtition Zone, a WesternDonetsk cover-folded Region was separated, covering two tectonic areas in intensity and style of deformation of the sedimentary cover – Kalmius-Toretsky area of scaly covering in the southwestern part, which is limited to the South Donbass Melange Zone in the south, and the Lugansk-Kamyshuvakhsky area of the coulisse-jointed uplift-folding on the northeastern part, which from the north is limited by the low-folded Mesozoic-Cenozoic cover. They are separated by the Central Zone of Strike-slip control along the axial folded zone of large stage-jointed uplift-folds, which include Great-Kamyshuvakhska, Novotroitska, Druzhkovsko-Konstantinovska and Main anticlines. Practical significance. Based on the actual geo-mapping data, it is proved that the riftogenic structure in the southeast of the Dnieper-Donets Paleorift is destroyed by folding at the stages of platform activation. Allocation of territory of the Western Donets Cover-folded Region allows correcting the scheme of tectonic zoning of the Dnieper-Donets Basin, which is the basis for modeling the geodynamics of the Transition Zone formation.
Геодинаміка формування перехідної зони між Дніпровсько-Донецькою западиною і Донецькою складчастою спорудою. Тектонічний стиль інверсійних деформацій
Keywords: решітка тектонітів; пластини та луски покривів насування; підкидо-складчастість; сегмент тектонічного вклинювання; Західно-Донецька покривно-складчаста тектонічна область; tectonite framework; thrust cover; uplift folds; tectonic wedging segment; cover-folded region; 551.24.548; 242.7; 248(477)